The Murdoch Media Empire and the Spectacle of Scandal. - KELLNER, DOUGLAS (International Journal of Communication (19328036), 2012)
The article discusses the scandals or referred as "Murdochgate" in American multinational mass media company News Corp. managed by chief executive officer Rupert Murdoch. Topics discussed include the accusations of employees regarding the tabloid newspapers hacking for information, the conviction of Clive Goodman and Glenn Mulcaire due to hacking the cell phones of the Royal family and the Murdoch's media empire as a major source of right-wing power.